Determination of Combination of Optimal Factor Level in Improvement and Uniform Effort of Product Quality Using Taguchi Method - Hasibuan, Abdurrozzaq; Asaad, Mhd.; Krianto Sulaiman, Oris; Haris Nasution, Abdul; Nasution, Muslih; Andriany, Liesna (International Journal of Engineering and Technology, 2018)
The quality engineering including all of quality control activity in every phase from research and product development, production process planning and the consumer’s satisfaction. In the taguchi method used a matrix called orthogonal array located in the level combination election from the variable’s input for every experiment’s. The experiment result of taguchi method find level combination from the most infivential factor’s in decorated ceramic quality are: the mixture composition of raw material;s (level 2), the comparison consist from kaolin = 10 ; felspar = 10 : tanah pucung = 3 ; water glass = 0.25 ; boor clay = 1.25; the composition of dye (level) the comparison cousist from : cobalt = 1 and tanah pucung = 5; the mold sfape (level 2) the kind it’s fave a long neck. Besides from the experiment result find the prediction of defect persentase based on total average defect is 6.78 for every burning but based on signal to noise is less or niore 6.619% for every burning.